2002
DOI: 10.1007/bf02295132
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional adaptive testing with constraints on test content

Abstract: mathematical programming, multidimensional adaptive testing, multidimensional item response theory, posterior expected Kullback-Leibler information,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 15 publications
1
124
0
3
Order By: Relevance
“…Currently, interactive items can be included by pointing to raw HTML stems, although these do not directly integrate with the responses to each item. Additionally, more holistic control over content constraints may be included by providing support for so-called shadow testing designs (e.g., Veldkamp and Linden 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, interactive items can be included by pointing to raw HTML stems, although these do not directly integrate with the responses to each item. Additionally, more holistic control over content constraints may be included by providing support for so-called shadow testing designs (e.g., Veldkamp and Linden 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, many models for scoring polytomous items (OSTINI; NERING, 2006) have been presented in the literature. When several abilities account for the response behavior, multidimensional IRT models can be applied (SEGALL, 1996; VELDKAMP; VAN DER LINDEN, 2002;RECKASE, 2009). …”
Section: Computerized Adaptive Testingmentioning
confidence: 99%
“…Item selection Many item selection rules have been proposed for CAT. Maximum Fisher information (BIRNBAUM, 1968) is most commonly applied, but Fisher interval information (VEERKAMP; BERGER,1997), Kullback-Leibler information (CHANG; YING, 1996; VELDKAMP; VAN DER LINDEN, 2002), or mutual information (WEISSMAN, 2007) might be applied as well. All these item selection rules have in common that they try to maximize information obtained about the candidate in order to minimize the error of estimation.…”
Section: Five Basic Steps Of Catmentioning
confidence: 99%
“…This information is used as a prior distribution to select next item which is believed to contribute to the precision of ability estimates. KL information measures the distance between two likelihoods at true ability and current ability and it is concluded that KL information is a better indicator discriminating true and estimated ability based on posterior densities and doesn't require ability levels close to each other (Veldkamp and van der Linden, 2002). Also KL information overcomes the attenuation paradox which helps to estimate correct θ values rather than using Fisher information.…”
Section: Introductionmentioning
confidence: 99%